تطور التنظيم القضائي في الجزائر - كوكب حزام; جهيدة رواينية (My University, 2025)
Abstract: The Algerian judicial system has witnessed several stages and transformations that reflected the legislator’s desire to establish several principles, the most important of which is guaranteeing the right to litigation and embodying the principle of justice. The adoption of actual judicial duality with the issuance of the 1996 Constitution and its amendments was followed by several reforms and developments affecting the ordinary judiciary and the administrative judiciary, the most important of which is the creation of specialized commercial courts and administrative courts of appeal. All these efforts came to develop and modernize this sector to keep pace with all the new global transformations .......................... ملخص: شهد التنظيم القضائي الجزائري عدة مراحل وتحولات عكست رغبة المشرع في تكريس عدة مبادئ اهمها ضمان حق التقاضي وتجسيد مبدا العدالة فتبنى الازدواجية القضائية الفعلية مع صدور دستور 1996وتعديلاته تلتها عدة اصلاحات ومستجدات مست القضاء عادي والقضاء الاداري اهمها استحداث المحاكم التجارية المتخصصة والمحاكم الادارية للاستئناف وكل هاته المساعي جاءت لتطوير هذا القطاع وعصرنته ليواكب كل التحولات العالمية الجديدة ......................... Résumé : Le système judiciaire algérien a connu plusieurs étapes et transformations reflétant la volonté du législateur d’établir plusieurs principes, dont le plus important est la garantie du droit au recours juridictionnel et l’incarnation du principe de justice. L’adoption d’une véritable dualité juridictionnelle avec la promulgation de la Constitution de 1996 et ses amendements a été suivie de plusieurs réformes et évolutions touchant tant la justice ordinaire que la justice administrative. Parmi les plus importantes, on note la création de tribunaux de commerce spécialisés et de cours administratives d’appel. Tous ces efforts visent à développer et moderniser ce secteur afin de suivre le rythme des nouvelles transformations mondiales.
Keywords: Key words: juridical unity; duality; updates; specialized commercial courts; administrative courts of appeal .; Mots-clés : unicité juridictionnelle; dualité; réformes; tribunaux de commerce spécialisés; cours administratives d’appel.; الكلمات المفتاحية: وحدة القضاء، ازدواجية، مستجدات، المحاكم التجارية المتخصصة، المحاكم الإدارية للاستئناف.